Inventory Information System for Health Equipment and Medicines Products Using the EOQ (Economic Order Quantity) Method in Pharmacy Installation of RSUD HAMS Web-Based Range: Inventory Information System for Health Equipment and Medicines Products Using the EOQ (Economic Order Quantity) Method in Pharmacy Installation of RSUD HAMS Web-Based Range - Jeperson Hutahaean; Neni Mulyani (Jurnal Mantik, 2020)
This study aims to determine the efficiency of inventory management of medical equipment and drugs in the pharmacy installation of RSUD HAMS Kisaran Hospital using the EOQ method. This study uses a qualitative approach, data obtained by conducting interviews and observations to the pharmacy installation of RSUD HAMS Kisaran Hospital. The data collected is then processed using the EOQ (Economic Order Quantity) method. Pharmacy installation is part of the hospital in charge of organizing, coordinating, regulating, and supervising all pharmaceutical service activities as well as carrying out pharmacy technical guidance in hospitals. At present the pharmacy installation of RSUD HAMS Kisaran Hospital has not efficiently controlled the supply of goods as its function. Procurement of goods is done by recapitulating the data of whatever items are needed, then made a purchase of the goods. Inventories of goods are calculated manually on average use of goods per month without any details regarding storage costs and inventory ordering costs for one item of goods. EOQ is a method used to determine the number of purchases of materials at each order with the lowest cost. The results of the research that has been done, using the Economic Order Quantity method can help the pharmaceutical installation of HAMS Public Hospital. The range is to find out the inventory data, the number of items to be ordered, when to order the goods, and how much it costs to meet these needs so that the process inventory management can be carried out more effectively and efficiently.